2012
DOI: 10.1111/j.1467-9566.2012.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Eggs, ethics and exploitation? Investigating women’s experiences of an egg sharing scheme

Abstract: There is a growing global demand for human eggs for the treatment of sub-fertile women and for stem cell-related research. This demand provokes concerns for the women providing the eggs, including their possible exploitation, whether they should be paid, whether they can give properly informed consent and whether their eggs and bodies are becoming commodified. However, few of the debates have benefitted from insights from the women themselves. We address this gap in knowledge by reporting on a study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…Our results, along with more recent technical advances in human NT9, provide proof of principle for the use of NT to develop isogenic ES cell-based therapies for the treatment of degenerative disease associated with mtDNA mutations. Furthermore, we demonstrated that the problem of obtaining human oocytes can be overcome by donation through an “egg-sharing” scheme, which has a high level of acceptance among women undergoing IVF treatment2941.…”
Section: Discussionmentioning
confidence: 98%
“…Our results, along with more recent technical advances in human NT9, provide proof of principle for the use of NT to develop isogenic ES cell-based therapies for the treatment of degenerative disease associated with mtDNA mutations. Furthermore, we demonstrated that the problem of obtaining human oocytes can be overcome by donation through an “egg-sharing” scheme, which has a high level of acceptance among women undergoing IVF treatment2941.…”
Section: Discussionmentioning
confidence: 98%
“…En effet, si la rétribution d'un don de gamète (et a fortiori d'une GPA) pose en elle-même des questions de principe, la crainte couramment exprimée porte également sur la pression qu'une rétribution importante peut exercer sur des femmes d'origine sociale modeste (Pennings et al, 2014). Certains chercheurs font toutefois remarquer qu'il ne faut pas sous-estimer ou nier l'autonomie de ces femmes (Haimes, Taylor et Turkmendag, 2012) ni la possibilité que peuvent leur apporter ces pratiques rémunérées de participer à la société de consommation (Nahman, 2013). Il s'agirait ainsi plutôt d'examiner et de comprendre le cadre dans lequel celles-ci évoluent et sont amenées à réaliser certains choix.…”
Section: Perspectives Bioéthiques Et Sociolégalesunclassified
“…Vu le peu de données empiriques disponibles en la matière, les recherches futures gagneraient certainement à examiner, dans différents contextes sociopolitiques et religieux, le point de vue des hommes impliqués dans des situations de procréation médicalement assistée afin de mieux comprendre leurs difficultés particulières et la manière dont ils vivent ces situations ainsi que l'impact que le recours aux techniques reproductives peut avoir sur eux en termes d'identité et de parenté (Culley, Hudson et Van Rooij, 2009 (Thompson, 2013;Franklin, 2006;Cooper et Waldby, 2014). Il existe par exemple encore très peu de données sur les manières dont sont recrutés les donneurs et donneuses de gamètes ainsi que sur leur profil et leurs motivations (Steinbrook, 2006;Haimes, Taylor et Turkmendag, 2012). Dans sa recherche aux États-Unis où la vente de gamètes est autorisée, Rene Almeling montre comment l'encadrement de ces pratiques et les discours qui les accompagnent sont significativement genrés.…”
Section: Les Enjeux En Suspensunclassified
“…Numerous debates have arisen over the social and ethical challenges involved in acquiring eggs for research (Haimes, Taylor, & Turkmendag, 2012; Waldby & Carroll, 2012), highlighted by the ‘Hwang scandal’ which revealed falsified results and the likely abuse of women persuaded to provide eggs (Baylis, 2009). One contentious issue is whether women should be given any financial, or other, return, either for the eggs, or for undergoing the possible risks of ovarian stimulation and egg collection (Egli et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We have addressed the question of ‘exploitation’ and the NESR elsewhere (Haimes et al., 2012). In this paper I present a wider range of data, to provide contextualised ‘specificities’ (Roberts & Throsby, 2008:160) of how the NESR is experienced, and shaped, by women volunteers.…”
Section: Introductionmentioning
confidence: 99%